Effect of the Chemical Nature of Fibres on Dynamic Water Vapour and Heat Transport Through Textiles - Haghi, A.K. (Asian Journal of Chemistry, 2016)
An improved mathematical model that takes into account the water vapour sorption mechanisms of wool fibre is developed to describe and predict the coupled heat and moisture transport in wool fabrics. On the basis of the model, the moisture-sorption mechanisms are investigated for fabrics made from fibres with different degrees of hygroscopicity. Theoretical predictions on the moisture uptake and temperature changes under humidity transients are compared with those measured previously in a sorption-cell experiment for fabrics made from wool, cotton, acrylic fibre and polypropylene fibre. It is concluded that the physical mechanism of moisture diffusion into highly hygroscopic fibres such as wool and cotton can be described by a two stage moisture diffusion process.